Analysis of Student’s Misconceptions in Solving a Discrete Random Variable - Arfatin Nurrahmah; Kartono Kartono; Zaenuri Zaenuri (International Conference on Science, Education, and Technology, 2021)
One of the most important obstacles in learning mathematics is misconceptions. This study aims to analyze student misconceptions in solving the problem of one discrete random variable in probability theory courses. The research was conducted on students of semester fifth of mathematics education study program at Indraprasta University PGRI Jakarta who took probability theory courses. The method in this study is qualitative. The study subjects were two people selected using snowball sampling techniques. The instruments used are tests on probability theory courses, interview guidelines, and observations. Testing the validity of research data using triangulation. Data analysis is done using data presentation, data reduction, and conclusion withdrawal. The results showed that the misconceptions experienced by subjects in discrete random variable material, namely in the process of determining the function of probability. First subject (S1) assumes that the probability function is equal to the probability value, whereas Second subject (S2) cannot distinguish properties on geometric and binomial discrete special distributions. Such misconceptions lead to a constant misconception in determining the function of probabilities. This will result in other misconceptions related to the probability function material, such as determining expectations and variances.